Deformação em canal angular de uma liga Al-4%Cu: efeito dos mecanismos de endurecimento na resistência mecânica e ductilidade - Prados, Erika Fernanda (2011)
Internal boundaries hardening and precipitation hardening are two important mechanisms acting in metallic alloys. The former has special relevance when the grain size is reduced to dimensions below 1 μm, and this can be accomplished by a variety of Severe Plastic Deformation techniques, such as Equal Channel Angular Pressing. The objective of the present thesis is a better understanding of the strengthening mechanisms and work-hardening behavior of a precipitation hardening Al alloy subjected to Equal Channel Angular Pressing. The pertinent literature almost invariably shows that high strength goes together with low work hardening rate, that is, the stress-strain curve tends to be flat, meaning that highly deformed metals and alloys show low ductility. Among the strategies devised to counteract this effect, post deformation precipitation heat treatments seem to have a beneficial effect on the work hardening rate. In this condition precipitates would reduce the dynamic recovery rate and additionally promote some hardening. The present study was performed on an Al-4%Cu alloy, deformed by up to four passes of equal channel angular pressing and heat treated according to different schedules, including post deformation ageing. The work is divided in three sections: (i) Severe plastic deformation influence on precipitation; (ii) Correlation of strength and ductility with the Al2Cu precipitates dispersion, while the work hardening behavior is described by the relevant Kocks-Mecking curves; (ii) Study of the contribution of each of the four hardening mechanisms on final strength: work hardening, solid solution, precipitation and internal boundaries hardening. Conclusions show that a fine precipitate dispersion increases the work hardening rate by limiting dynamic recovery rate. It was also ascertained that cold deformation accelerates precipitation by a factor of three, however, precipitation hardening is swamped by the softening effect caused by the precipitation heat treatment itself.